The study on fish diversity in the Vishnupuri dam, Nanded (M.S.) India. - Pawar SK (International Journal of Life Sciences, 2017)
India has vast potential for development of inland fisheries. In marthwada region some of the agriculture farmers with the help of F.I.D.A. are constructing fish ponds, in their agriculture farms. River godavari is originated from Trimbakeshwar, dist Nasik. It flows 7 districts in Maharashtra, one of the districts Nanded. Godavari river flow 10.5km in Nanded. The present study is an attempt to document the fish fauna in the Vishnupuri dam during the year June 2015 to May 2016. In present investigation about 29 species of fish.